Strategi Meningkatkan Penemuan Kasus Baru Tuberculosis BTA Positif di Masyarakat: Strategy to Increase the Discovery of New Cases of BTA Positive Tuberculosis in the Community - Mordekai Rangkoratat, Melinda; Puspitasari, Yenny; Yosua Hanoatubun, Yakob (Jurnal Abdi Keperawatan dan Kedokteran, 2024)
Pulmonary tuberculosis (pulmonary TB) is a curable condition, but often patients stop treatment before it is finished. This is due to the patient's misconception about healing; They think that their illness has been cured because their symptoms have disappeared or decreased. In fact, pulmonary tuberculosis therapy must be carried out for a minimum of six months. This study aims to identify how strategies to increase the discovery of new cases of BTA-positive tuberculosis in the community are applied.  The methods used include fishbone diagrams, Urgency, Seriousness, Growth (USG) methods, and Strength, Weakness, Opportunity, Threat (SWOT) analysis. Based on the analysis carried out, problems were found related to the strategy of increasing the discovery of BTA+ pulmonary TB cases at the Lalasan Health Center, Tanimbar Islands Regency, Maluku Province.  Based on the identification of the problem, the priority of the problem was determined using the Multiple Criteria Utility Assessment (MCUA) method, namely the low coverage of Pulmonary TB CDR at the Lingat Health Center, Tanimbar Islands Regency in 2024. Suggested solutions to address this problem include improving strategies for the discovery of new cases of BTA-positive tuberculosis. This study specifically examines the implementation of these strategies and determines the means and media to disseminate information about TB at the Lingats Health Center, Tanimbar Islands Regency, Maluku Province, by involving health workers and the community.